THE INFLUENCE OF SHOPPING LIFESTYLE, FASHION INVOLVEMENT, DISCOUNT, LIVE STREAMING SHOPPING, AND PAYMENT METHODS ON IMPULSE BUYING FASHION PRODUCTS ON THE SHOPEE MARKETPLACE - Hady, Intan Ferial; Izzuddin, Ahmad; Wibowo, Yohanes Gunawan (Univesitas Muhammadiyah Tangerang, 2024)
This research aims to determine the influence of shopping lifestyle, fashion involvement, discounts, live streaming shopping, and payment methods on Impulse Buying of fashion products on the Shopee Marketplace (case study of Generation Z in Sumbersari District, Jember Regency). The type of research used in this research is quantitative. The population in this study is Generation Z Shopee application users in Sumbersari District, Jember Regency and the sample taken was 155 people with a sampling technique using purposive sampling. Data collection methods are through observation and questionnaires via Google Form. The data analysis used is multiple linear regression, while hypothesis testing uses the t test. The research results show that Shopping Lifestyle, Fashion Engagement, Discounts, Live Streaming Shopping, and Payment Methods have a significant influence on Impulse Buying of fashion products on the Shopee Marketplace. Suggestions for future researchers are adding variables that support measuring Impulse Buying, such as Electronic Word of Mouth (e-WOM) variables and Hedonic Shopping Motivation so that they can provide a broader picture of what factors influence Impulse Buying.